Estimating the cost function of connecticut public K-12 education: Implications for inequity and inadequacy in school spending - Bo Zhao (Federal Reserve Bank of Boston, 2020)
This paper's study of Connecticut's education costs can serve as the foundation of an equitable and adequate state education aid formula. To the best of the author's knowledge, it is the first cost function study of Connecticut public K-12 education. The author uses a regression model to estimate how much it costs each district to achieve a common student performance target level, as measured by statewide standardized testing, given student characteristics and other cost factors that are outside the direct control of local officials at any given point in time. The analysis shows the disparities in education costs across school districts and the equity and adequacy of each district's spending relative to its costs for achieving a common student performance target level.
Keywords: H75; I21; I22; I28; 330; cost function; education costs; school spending; equity in education finance; adequacy in education finance